Comprehensive analysis of spectral and photometric characteristics of the B[E] PHENOMENON object MWC 342 over a 40-year observation period - Akniyazova A.Ж.; Miroshnichenko A.С.; Zhanabaev З.Ж. (Recent Contributions to Physics, 2025)
MWC 342 (V1972 Cyg) is an early-type emission-line star discovered approximately 90 years ago. The object exhibits the characteristic B[e] phenomenon, including both permitted and forbidden emission lines, as well as an infrared excess caused by emission from circumstellar dust, first identified in the 1970s. However, its evolutionary status remains under debate. Over the years, MWC 342 has been classified as a Herbig Be star, a binary system with a cool companion, or a long-period variable star. This paper presents the results of spectroscopic and photometric analyses of the object based on data collected from 1986 to 2024. Medium- and high-resolution spectra were compared with optical brightness variations. We identified quasi-periodic photometric variability on a characteristic timescale of 20 years and established a correlation between optical brightness and the equivalent width of the Hα line, likely related to changes in the density of the circumstellar environment. An analysis of the spectral energy distribution (SED) up to 160 µm revealed a sharp decline in flux at longer wavelengths, indicating the absence of a significant amount of cold circumstellar dust in the system. This supports the hypothesis of a compact dust disk. A theoretical SED with an effective temperature of 25,000 K fits the photometric data well in the optical range. Using the Gaia DR3 distance and a new map of interstellar reddening in the direction of the object, we refined its luminosity to log(L/L0)=3.9. These results highlight the importance of continued spectroscopic and multicolor photometric monitoring of MWC 342 to further clarify its nature and the dynamics of its circumstellar environment.